EVALUASI KONDISI DAN KERUSAKAN PERKERASAN LENTUR DI BEBERAPA RUAS JALAN KOTA KENDARI - Djalante, Susanti (MEKTEK, 2011)
The roles of the road as the major transportation are to speed up economic between areas, so the goodroad pavement condition is required. Base on the statistic 2010, the roads in Sulawesi Tenggara much morefailure condition than good condition. To minimize the road failure condition, the objective of this researchis to determine the road condition (PCI) and to know causal factors in order to get the best treatmentpriority.This research used Pavement Condition Index Method. The steps of PCI Method were at the first devidedthe road to some units (160 units), second calculate density with the distress type , third measured totaldeduct Value and Corrected Deduct Value base on curve, the last got PCI Indeks.Result of the study showed that the distress types included the alligator cracking(36%), transverse cracking(13%, diagonal cracking (0,1%), block cracking (15,1%), edge cracking (3,5%), depression (2,6%),corrugation ( 1,4%), shoving (1,6%), rutting (0,2%), raveling (56,9 %), bleeding (2,9 %), potholes (6,9 %)and patching (8,5%). However, The PCI of flexible pavement in kendary city was 72 (very good ) and thesubdistrict which got the treadment priority was Puwatu, Wua-Wua and Baruga